2023
DOI: 10.3390/a16070343
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for Detecting Verticillium Fungus in Olive Trees: Using YOLO in UAV Imagery

Marios Mamalis,
Evangelos Kalampokis,
Ilias Kalfas
et al.

Abstract: The verticillium fungus has become a widespread threat to olive fields around the world in recent years. The accurate and early detection of the disease at scale could support solving the problem. In this paper, we use the YOLO version 5 model to detect verticillium fungus in olive trees using aerial RGB imagery captured by unmanned aerial vehicles. The aim of our paper is to compare different architectures of the model and evaluate their performance on this task. The architectures are evaluated at two differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…Symptoms of olive Verticillium wilt of olive can vary depending on the stage of infection, and environmental conditions. However, some common symptoms associated with Verticillium wilt of olive include (Figure 1) (Castro et al, 2020;ElDesouki-Arafat et al, 2021;Cardoni et al, 2022;Markakis et al, 2022;Mamalis et al, 2023): Wilting: Affected trees may exhibit wilting, where leaves on one or more branches or the entire tree droop and lose turgidity even when the soil has adequate moisture. Yellowing and rolling: Leaves may turn yellow or bronze, often starting at the margins or between the veins causing them to curl.…”
Section: Symptomsmentioning
confidence: 99%
See 3 more Smart Citations
“…Symptoms of olive Verticillium wilt of olive can vary depending on the stage of infection, and environmental conditions. However, some common symptoms associated with Verticillium wilt of olive include (Figure 1) (Castro et al, 2020;ElDesouki-Arafat et al, 2021;Cardoni et al, 2022;Markakis et al, 2022;Mamalis et al, 2023): Wilting: Affected trees may exhibit wilting, where leaves on one or more branches or the entire tree droop and lose turgidity even when the soil has adequate moisture. Yellowing and rolling: Leaves may turn yellow or bronze, often starting at the margins or between the veins causing them to curl.…”
Section: Symptomsmentioning
confidence: 99%
“…Verticillium wilt is of significant economic importance due to its widespread distribution, broad host range, and potential to cause severe damage. Here are some key reasons why Verticillium wilt is economically important (Castro et al, 2020;ElDesouki-Arafat et al, 2021;Cardoni et al, 2022;Markakis et al, 2022;Mamalis et al, 2023): Crop losses: V. dahliae can infect and cause wilt in a wide range of economically important crops, including olive trees. The disease can lead to yield losses, reduced quality of produce, and even complete crop failures, resulting in significant economic losses for farmers and growers (ElDesouki-Arafat et al, 2021).…”
Section: Economic Importancementioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it predicts the class probabilities of the detected object. In agriculture [3][4][5][6][7][8], UAVs equipped with YOLO models have enhanced monitoring and disease detection. Studies have shown the algorithm's effectiveness in early disease detection in crops like rice, olives, maize, and apple trees.…”
Section: Introductionmentioning
confidence: 99%